Money and banking in Ireland - origins development and future - McGowan, Padraig (Statistical and Social Inquiry Society of Ireland, 1989)
Currency and banking have a relatively long tradition in Ireland. Coins have circulated for about 1,000 years and banking has been practised for some 300 years. Significant financial change was a feature of earlier periods as it has been over the past twenty five years. Current indications are that the rate of structural change in the financial sector will gain momentum between now and the end of this century. An appreciation of the past can contribute to understanding the present. Influence over future events can be improved by a greater awareness of how we adapted to change in the past. With this in mind, a brief review of the evolution of currency and banking in Ireland, both in the Republic and Northern Ireland, is presented here together with a preview of some of the major changes that will be occurring in the decades ahead. The emphasis is on the structural changes that occurred rather than an evaluation of the policies pursued but many of the issues raised are relevant to the debate about the expected changes in the financial sector in the 1990s. A wide range of publications on Irish banking has been drawn upon, many of which are cited in the Bibliography. The review is divided into three parts. Part I concentrates on the historical background and outlines the origins and development of money and banking in Ireland up to the middle of this century. Part II concentrates on the significant changes in banking and other financial institutions that have occurred in Ireland in recent decades, including the 1980s. Finally, Part III looks towards the twenty first century and integration within Europe with the emphasis on prudential supervision of banks, other financial institutions and the capital markets.
Read before the Society, 1 December, 1988
Keywords: Banking history; Future of banking; 314.15